Understanding the exodus: a 15-year retrospective cohort study on the pattern and determinants of migration among Nigerian doctors and dentists - Oghenebrume Wariri; Patience Toyin-Thomas; Itua C.G. Akhirevbulu; Oladapo Oladeinde; Oluchi Omogbai; Philippa Odika; John Osakue; Avwebo Ukueku; Efetobo Orikpete; Chinelo Iwegim; Efe E. Omoyibo; Jermaine Okpere; et al. (Global Health Action)
Background Nigeria faces a critical shortage of healthcare professionals yet experiences a significant annual exodus of doctors and dentists. This alarming trend threatens the country’s ability to provide equitable healthcare. Objective This study investigated the patterns and determinants of migration among doctors and dentists who graduated from the University of Benin, Nigeria, 15 years ago. Methods We conducted a retrospective cohort study that tracked 274 of the 379 (72.3%) eligible cohort. We computed the migration incidence rate per person-year from 2008 to 2023, covering 3,455 person-years of follow-up and analysed migration drivers as push and pull factors across macro-, meso-, and micro-levels. Results Fifteen years post-graduation, 48.9% (134/274) of the cohort had migrated. While the annual incidence rate of migration remained stable for the first 8 years, it spiked after 2016, reaching 11.4 per 100 person-years in 2023. Among those who migrated, the majority (96.3%, 129/134) relocated outside the African continent. The top three destination countries were the UK (48.5%, 65/134), Canada (20.9%, 28/134), and the USA (19.4%, 26/134). The leading push factors were insecurity of lives and property (57.8%), concerns about children’s futures (50.3%), and limited career development opportunities (45.9%). The primary pull factors included security (56.3%), permanent residency (49.6%), and better pay in the destination country (46.7%). Significant predictors of migration included younger age, timing of marriage, and residency training status. Conclusions To avert an impending crisis, the Nigerian government must address the root causes driving the increasing migration of doctors and dentists.